Polityka cen w Polsce w latach 1981 - 1983 - Krasiński, Zdzisław (Wydział Prawa i Administracji UAM, 1983)
Discussion in the article is focused on the reform of retail prices introduced on February 1, 1982. Analysis of changes in a price level and movements of prices in particular range of goods was preceded by a study of premises of the price reform. The following were specified in the group of these premises: the rapid exhaustion of stocks-in-trade in the years 1975 - 1981, a wide employment of fcrign crediting and a slight increase in the domestic market production. At the same time consumer incomes were increasing at a fast rate what caused a bias toward inflationary gap and pressure. The reform of retail prices introduced recently caused a high growth of prices and a reduction of consumers' real incomes. This has also effected a decrease of foodstuffs' subsidies, and subsidies of some non-food products and services, yet these subventions were not altogether eliminated. The prise rises and enacting a category of contract prices has not led to a market equilibrium situation. In case of some products a partial market recovery was observed and also a reduction of line ups in front of stores. Return to a market equilibrium position does not seem probable in view of slight stocks-in-trade, at least in the nearest future. Changes of price level have also effected the standard of living of consumers and caused transformations of a consumption model. The increase of food products' prices resulted in adding to a portion foodstuffs' expenses in all types of households.
Price policies in Poland in the years of 1981-1983